CONTRIBUTION OF EVA LEVERAGE TO THE TOTAL LEVERAGE EFFECT ON THE COMPANY - Kristina Jančovičová BOGNÁROVÁ (Challenges of the Knowledge Society)
The concept of Economic Value Added (EVA) and Market Value Added (MVA) has opened up new insights into the leverage effect of fixed costs (operational leverage) and interest (financial leverage), and for determining what effects the changes in sales would have through leverage, not only on profits, but also on EVA and MVA. The paper also introduces the leverage effect of the cost of equity as a new concept and illustrates how it reacts in conjunction with operating leverage and financial leverage to determine the total overall leverage of the company. A spreadsheet model was developed using a given level of operating leverage and financial leverage. The relationship between profits (after interest and tax) and EVA was determined by using the cost of own capital (equity), and this fixed amount can therefore be described as a leverage factor for EVA. Furthermore, the EVA leverage factor was combined with the operating and financial leverage in order to illustrate how the expected percentage change in EVA and MVA can be predicted, given a certain percentage change in sales (or profits). The results of the model were than analysed to reach conclusions.